Clinically accurate diagnosis of Alzheimer’s disease via multiplexed sensing of core biomarkers in human plasma - Kim, Kayoung; Kim, Min-Ji; Kim, Da Won; Kim, Su Yeong; Park, Steve; Park, Chan Beum (Nature communications, 2020)
Alzheimer’s disease (AD) is the most prevalent neurodegenerative disorder, affecting one in ten people aged over 65 years. Despite the severity of the disease, early diagnosis of AD is still challenging due to the low accuracy or high cost of neuropsychological tests and neuroimaging. Here we report clinically accurate and ultrasensitive detection of multiple AD core biomarkers (t-tau, p-tau 181 , Aβ 42 , and Aβ 40 ) in human plasma using densely aligned carbon nanotubes (CNTs). The closely packed and unidirectionally aligned CNT sensor array exhibits high precision, sensitivity, and accuracy, evidenced by a low coefficient of variation (<6%), a femtomolar-level limit of detection, and a high degree of recovery (>93.0%). By measuring the levels of t-tau/Aβ 42 , p-tau 181 /Aβ 42 , and Aβ 42 /Aβ 40 in clinical blood samples, the sensor array successfully discriminates the clinically diagnosed AD patients from healthy controls with an average sensitivity of 90.0%, a selectivity of 90.0%, and an average accuracy of 88.6%. Detection of Alzheimer’s disease (AD) biomarkers from patients’ blood is challenging because these are present in very low concentrations in the plasma. Here the authors develop a sensor array of densely aligned single-walled carbon nanotubes for clinically accurate detection of femtomolar AD biomarkers in human plasma samples.